Att göra klass: nedslag i svensk semtidsprosa. - Arping, Åsa (Kriterium, 2022)
How is class depicted in Swedish contemporary literature, and what can it teach us about contemporary society? In Doing Class, literary scholar Åsa Arping tries new pathways into the broad, mainly realistic Swedish novels of recent decades. She finds class-coded actions, thoughts and emotions even outside the traditional working-class literature, and explores how the story of class deepens when it is put into dialogue with other categories, such as gender, age and ethnicity/racialization.Through reflections on the last twenty years of prose publishing, from Torbjörn Flygt's Underdog (2001) to Donia Saleh's Ya Leila (2020), the study shows how literature shapes and discusses the increasingly obscure class concept, where perceptions of work, identity, lifestyle and welfare state are rapidly changing.